(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Although silk fibroin (SF) materials have gained extensive attention in tissue engineering due to their good machinability, biocompatibility, biodegradability, the complex processes, unmatched pore structures, and chemical crosslinker still hinder their mass production and clinic use. In this study, we reported a direct green and high-efficiency process to fabricate 3D silk fibroin scaffold by solvent exchange in water. The pore parameters were easily regulated with NaCl as auxiliary porogen. More importantly, without using any crosslinker or organic chemical-induced crystallin, SF scaffolds is mainly constructed with stable silk II crystalline (constituent with β-sheets), which was confirmed by Flourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Additionally, the scaffold in our research keeps good tunability on mechanical properties, which has been demonstrated by the results of mechanical testing and provides a feasible way to optimize physical cues for further applications. Thus, the 3D porous silk scaffold with high efficiency and promising structures broaden the potential as a substitute for biomaterials.